Krugovaja trenirovka kak sposob modelirovanija fiziceskoj nagruzki v figurnom katanii - Cherepanova, I. O.; Dunaev, K. S.; Seyranov, S. G.; Tikhomirov, A. K. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
This article discusses the application of the circular training method for the development of power qualities of skaters aged 9-10 years old at the stage of sports specialization. Circular training is aimed at developing independent thinking among athletes, developing physical abilities, and developing algorithms for motor actions. It is very significant that it allows for the individualization of training and education, and the efficient use of the time planned for physical training in the training process. In the process of circular training, the trainer gives the athletes a specific program of action, monitors its implementation, evaluates the completed, corrects if necessary, clarifies individual exercises or regulates the actions of the skater.